Changes in The Meaning of Words in Slang: A Synchronous Semantic Study - Dewi Kristina Hutapea; b Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze how the meanings of selected slang words have changed over a specific period, identify the types of semantic change, and explain the social, cultural, and technological factors influencing those shifts. A qualitative descriptive method was applied to examine ten commonly used slang terms. The analysis revealed that the dominant type of semantic change was broadening, where the original meaning of a word expanded to cover broader or new usage contexts. Other types of semantic shifts, such as narrowing and metaphorical extension, were also observed. Slang words like baper, ghosting, receh, and santuy exemplify how language adapts to modern communication needs and reflects youth identity, emotion, and humor. The findings support the view that slang is not merely linguistic play but a reflection of social interaction and cultural trends. Through a synchronous analysis, this study shows how language functions as a living system that responds to changes in society, behavior, and media usage. Understanding these shifts is essential for both linguists and educators in appreciating the role of informal language in shaping modern communication.